DEVELOPMENT OF THE FUTURE MANAGERS’ DEONTOLOGICAL CULTURE IN THE PROCESS OF TEACHING A FOREIGN LANGUAGE - Maryna Shepel (Неперервна професійна освіта: теорія та практика)
The article deals with the role of deontological culture in the process of teaching a foreign language at a technical university as a factor of future managers’ formation. The article makes an analysis of domestic and foreign scientific literature devoted to the problems of deontological culture and professional ethics. The author gives her own notion to the concepts of «future managers’ deontological culture» and «future managers’ professional ethics». When choosing a method of teaching the foreign (English) language for specific purposes, aimed at the deontological culture development, a communicative approach was chosen. In the process of deontological culture development much attention is paid to business games and role-plays. The aim of these games is to model future managers’ professional situations that are related to the development of business communication ethics, behaviour and communication culture. In the process of games we develop the skills of trusting and empathetic communication, the ability to listen to future colleagues and clients. Much attention is paid to working with professionally-oriented texts. In the process of development of future managers’ logical and critical thinking, their personal and professional qualities we use such methods as: case method, project method, brainstorming, vocabulary replenishment, microphone. The author believes that these methods of deontological culture development in the process of teaching a foreign language will contribute to: improvement of students’ personal qualities, competences development, formation of behavioural skills in managers’ professional activity according to norms and rules of deontological culture. Further study becomes the problem of future managers’ business writing skills development as a prerequisite for becoming professionals